Integrated Analysis of microRNAs and Transcription Factor Targets in Floral Transition of Pleioblastus pygmaeus - Wenjing Yao; Peng Shen; Meng Yang; Qianyu Meng; Rui Zhou; Long Li; Shuyan Lin (Plants)
Bamboo plants have erratic flowering habits with a long vegetative growth and an uncertain flowering cycle. The process of floral transition has always been one of the hot and intriguing topics in bamboo developmental biology. As master modulators of gene expression at the post-transcriptional level, miRNAs play a crucial role in regulating reproductive growth, especially in floral transition of flowering plants. Pleioblastus pygmaeus is a kind of excellent ground cover ornamental bamboo species. In this study, we performed miRNA expression profiling of the shoot buds and flower buds from the bamboo species, to investigate flowering-related miRNAs in bamboo plants. A total of 179 mature miRNAs were identified from P. pygmaeus, including 120 known miRNAs and 59 novel miRNAs, of which 96 (61 known miRNAs and 35 novel miRNAs) were differentially expressed in the shoots at different growth stages. Based on target gene (TG) prediction, a total of 2099 transcription factors (TFs) were annotated to be TGs of the 96 differentially expressed miRNAs (DEMs), corresponding to 839 recordings of DEM-TF pairs. In addition, we identified 23 known DEMs involved in flowering and six known miRNAs related to floral organ development based on previous reports. Among these, there were 11 significantly differentially expressed miRNAs, with 124 TF targets corresponding to 132 DEM-TF pairs in P. pygmaeus. In particular, we focused on the identification of miR156a-SPL (SQUAMOSA Promoter-Binding protein-Like) modules in the age pathway, which are well-known to regulate the vegetative-to-reproductive phase transition in flowering plants. A total of 36 TF targets of miR156a were identified, among which there were 11 SPLs. The Dual-Luciferase transient expression assay indicated miR156a mediated the repression of the PpSPL targets in P. pygmaeus. The integrated analysis of miRNAs and TGs at genome scale in this study provides insight into the essential roles of individual miRNAs in modulating flowering transition through regulating TF targets in bamboo plants.